THE ECONOMIC RELATIONSHIP BETWEEN EXCHANGE RATE AND MONEY SUPPLY AND THEIR IMPACT ON AGRICULTURAL PRODUCTS IN IRAQ - R. T. Al-Wasity; Hala A. Al-Attabi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research aimed to measure and analyze the impact of exchange rate shocks on some variables of the Iraqi economy during (1990-2022), because of the different effects of these shocks on the macroeconomic variables represented in money supply and agricultural output. Exchange rates are related to the policy chosen by the Central Bank of Iraq in managing the foreign exchange market and in the rentier nature of the Iraqi economy. The research uses a quantitative method in estimating the levels of the impact of exchange rate shocks on some economic variables. Several methods are conducted to achieve the goals, including the VAR model, variance decomposition and Impulse Response Functions. The results showed that exchange rate variance reached 100% in the same variable in the first year and decrease to 97% at the end of the period, and the same in the impulse response. It was an internal reaction that predicts what can be called the self-wave of an exchange rate rise, while both the variation and the response to the money supply shock in Iraq were dependent on the policy of the Central Bank and compatible with what was happening in the exchange rate, as the analysis of variance in the first year reached 38.98% for the same variable and 61% of it is due to the exchange rate. The results also showed that agricultural output was weakly affected by the exchange rate shock and money supply.